THE CORRELATION BETWEEN STUDENTS’ READING HABIT AND CRITICAL THINKING SKILLS - Hasanah, Rulita; Martina, Feny; Liska Afriani, Zelvia (JPT : Jurnal Pendidikan Tematik, 2022)
This research aims to determine whether there is a positive correlation between students' reading habit and critical thinking skills. The method used in this research is a quantitative approach with the correlation method. The sample consisted of 30 eleventh grade IPA students at SMAN 12 Rejang Lebong. The instruments used in this research, namely a questionnaire used to measure the level of reading habit and a writing test to measure the level of students' critical thinking skills. There are several results from this research, including the following; the reading habit of the eleventh grade IPA students of SMAN 12 Rejang Lebong is quite good with an average of 74.37. Some students have very good reading habits, but there are still some students who have poor reading habits. Second, students' critical thinking skills in writing analytical exposition texts in eleventh grade IPA students at SMAN 12 Rejang Lebong are low because they have an average score of 62.57, but some students have good critical thinking skills. And the last, the correlation between students reading habit and critical thinking skill. There is a positive significant correlation between the both variables with a sig. (2-tailed) value of 0.00 < 0.05 and a Pearson correlation of 0.615. So it can be concluded that there was a positive significant correlation between students' reading habit and critical thinking skills in eleventh grade IPA students at SMAN 12 Rejang Lebong with a high correlation.